Efficacy and Safety of the All-Oral Schedule of Metronomic Vinorelbine and Capecitabine in Locally Advanced or Metastatic Breast Cancer Patients: The Phase I-II VICTOR-1 Study. (16th January 2014) - Cazzaniga, M. E.; Torri, V.; Villa, F.; Giuntini, N.; Riva, F.; Zeppellini, A.; Cortinovis, D.; Bidoli, P.
Abstract : Background . Vinorelbine (VRB) and capecitabine (CAPE) are demonstrated to be active in pretreated metastatic breast cancer patients. Different studies have demonstrated that the metronomic treatment is active with an acceptable toxicity profile. We designed a Phases I-II study to define the MTD of oral metronomic, VRB, and CAPE. Patients and Methods . Phase I: fixed dose of CAPE was 500 mg thrice a day, continuously. Level I of VRB was 20 mg/tot thrice a week for 3 weeks (1 cycle). Subsequent levels were 30 mg/tot and 40 mg/tot (Level III), respectively, if no Grades 3-4 toxicity were observed in the previous level. Phase II: further 32 patients received the MTD of VRB plus CAPE for a total of 187 cycles to confirm toxicity profile. Results . 12 patients were enrolled in Phase I and 22 in Phase II. Phase I: the MTD of VRB was 40 mg. Phase II: 187 cycles were delivered, observing 5.9% of Grades 3-4 toxicity. 31 patients are evaluable for efficacy, obtaining a clinical benefit rate of 58.1%. Conclusion . MTD of VRB with fixed dose of CAPE was 40 mg thrice a week and was the recommended dose for the ongoing Phase II multicenter study.